A systematic review of the research on telework and organizational economic performance indicators - Mutiganda, Jean Claude; Wiitavaara, Birgitta; Heiden, Marina; Svensson, Sven; Fagerström, Arne; Bergström, Gunnar; Aboagye, Emmanuel (Frontiers in Psychology, 2022)
A systematic review is conducted in the study to investigate the relationship between telework and organizational economic performance indicators such as self-reported employee performance, organizational performance, actual employee turnover rates, or intentions. The databases Scopus, Business Source Premier, and Web of Science were used to conduct a literature search. Original articles published from 2000 and up to May 2021 were selected. Studies were screened for inclusion independently by review pairs and data were extracted. The Mixed Methods Appraisal Tool (MMAT) was used to evaluate the quality of the studies included. Forty-three studies were included with some addressing multiple outcomes. Self-reported performance was higher for teleworking employees compared to those working in the ordinary workplace. The extent of the change in performance was dependent on individual characteristics and the extent of the teleworking practice in the organization. Telework was also associated with increased organizational performance, particularly in homogenous samples with unique work tasks. When telework is voluntary, it appears that both actual employee turnover rates and intentions to leave the organization are lower. Further research with high-quality prospective designs is necessary to properly understand the contribution of telework to organizational economic performance indicators.